A Framework for Ethical Online Course Development with Universal Design for Learning - Anselmo, Lorelei; Eaton, Sarah Elaine (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie)

(untitled) (The Canadian Network for Innovation in Education, 2025)
Postsecondary institutions increasingly recognize the importance of designing educational experiences that reflect students' diverse identities and life experiences. As online course enrollment continues to rise, it becomes crucial to address how course design can effectively support this diverse student population. Traditional course designs often fail to accommodate the broad spectrum of student backgrounds, resulting in barriers to success and inclusion. In response to this gap, we propose a framework for online course design that prioritizes inclusivity, flexibility, and ethical considerations. This three-layer framework systematically integrates Universal Design for Learning principles with academic integrity values and Indigenous academic integrity principles, providing educators with practical guidance to create ethical and supportive online learning environments that address learner agency while maintaining academic standards.